Overview of OTFS Based Channel Estimation Techniques in LEO Satellite Communication - Xinjie ZHAO; Ziwei LIU; Gengxin ZHANG (天地一体化信息网络)
With the development of science and technology and the continuous improvement of related technologies, low earth orbit (LEO) satellite communication has become a hot technology that countries all over the world are chasing.The advantages of orthogonal time frequency spacetechnology can well solve the signal transmission problem of broadband satellite ground link in high moving speed scenarios, which is conducive to the unifi cation of modulation waveforms between satellites and the ground, and the realization of space-based integrated communication.However, its transmission performance is aff ected by the accuracy of channel estimation, and the special modulation makes its channel estimation method diff erent from the traditional technology, so it needs to be studied.The existing mainstream OTFS channel estimation schemes are introduced, and the advantages and disadvantages of each scheme were analyzed, which laied a foundation for subsequent research.